Regional policy of the European Union - Međak Vladimir (Međunarodni Problemi)
The author analyses the development of the European Union’s regional policy since 1988 and possible changes that could occur after the eastward enlargement. He examines Delors I and Delors II budgetary packages, covering the period 1988-2000, main principles and objectives, their changes over time and instruments of conducting the policy - Structural Funds. The author also analyses the preparations for enlargement within the scope of Agenda 2000 report, its contents, negotiation process for its adoption and changes made by it. At the end, he examines the effect that regional policy has made so far and possible obstacles for the forthcoming enlargement.